Peculiarities of Chemisorption of Dimethyl Carbonate on Silica Surface - Protsak, I.S.; Pakhlov, E.M.; Tertykh, V.A. (Physics and Chemistry of Solid State, 2016)
This paper presents the results of studies of dimethyl carbonate interaction with sites of the fumed silica surface. The investigations were performed in a vacuum quartz cuvette using IR spectroscopy method. Chemical interaction of dimethyl carbonate with sites of the dehydrated silica surface was shown to occur at temperature of 200 °C and higher, chemisorption processes take place involving both structural silanol groups and siloxane bridges on the surface.